Experimental study of eigenstrains in temporomandibular joint discs using digital image analysis. (October 2022) - Tappert, L.; Dusfour, G.; Baldit, A.; Le Floc'H, S.; Lipinski, P.
Abstract: The temporomandibular joint is one of the most frequently used joints of the human body. Its malfunction can severely influence patient's well-being. Since the temporomandibular joint disc plays a major role in its functioning, especially in load distribution within the joint, it appears to be a crucial element to understand. This paper aims to improve understanding of the tissues within close in vivo conditions (i.e. hydrated at 37 ° C) by (i) comforting literature by revealing the presence of residual stresses within the temporomandibular joint disc, (ii) quantifying eigenstrains through a relaxation process and finally (iii) evaluating the internal mechanical state in intact temporomandibular joint discs central part, considering the tissue as a thin layer. Both global specimen size measurements and local digital image correlation were used to quantify 6 samples' deformation through a detailed analysis of approximately 30 images, recorded for approximately one hour, per disc. Thanks to a backward time approach combined to an analytical model, eigenstrains were assessed on discs. For the first time, the presence of complex initial strain fields within cylindrical specimens of porcine temporomandibular joint discs was quantified, confirming indications from literature. Digital image analysis revealed the partial internal stress release through specimen self-deformation. Close to zero in central part, it reached approximately 13% radial strain in the outer ring within a characteristic relaxation time close to 530 s . The principal strains' distribution agrees with the alignment of the collagen fibers in the central part of the discs revealed in many works. It led to deduce that, in the central area of the discs, the matrix undergoes a radial compression within physiological conditions to compensate the daily loading stresses. Therefore, this work improves understanding of the tissues in vivo conditions highlighting extraction cut effect on temporomandibular joint disc's tissues mechanical state. Graphical abstract: Highlights: Highlighting of the residual stresses within the temporomandibular joint disc. Global observation of the associated strain thanks to ring coring. Quantification of eigenstrains thanks to digital image correlation. Evaluation of the internal mechanical state in intact temporomandibular joint discs central part. Extraction cut effect on temporomandibular joint disc's tissues mechanical state.